Targeting the Potassium Channel Kv1.3 Kills Glioblastoma Cells - Elisa Venturini (Neurosignals, 2017)
Background/Aims: Glioblastoma (GBM) is one of the most aggressive cancers, counting for a high number of the newly diagnosed patients with central nervous system (CNS) cancers in the United States and Europe. Major features of GBM include aggressive and invasive growth as well as a high resistance to treatment. Kv1.3, a potassium channel of the shaker family, is expressed in the inner mitochondrial membrane of many cancer cells. Inhibition of mitochondrial Kv1.3 was shown to induce apoptosis in several tumor cells at doses that were not lethal for normal cells. Methods: We investigated the expression of Kv1.3 in different glioma cell lines by immunocytochemistry, western blotting and electron microscopy and analyzed the effect of newly synthesized, mitochondria-targeted, Kv1.3 inhibitors on the induction of cell death in these cells. Finally, we performed in vivo studies on glioma bearing mice. Results: Here, we report that Kv1.3 is expressed in mitochondria of human and murine GL261, A172 and LN308 glioma cells. Treatment with the novel Kv1.3 inhibitors PAPTP or PCARBTP as well as with clofazimine induced massive cell death in glioma cells, while Psora-4 and PAP-1 were almost without effect. However, in vivo experiments revealed that the drugs had no effect on orthotopic brain tumors in vivo. Conclusion: These data serve as proof of principle that Kv1.3 inhibitors kills GBM cells, but drugs that act in vivo against glioblastoma must be developed to translate these findings in vivo.